Multi-Area Economic Dispatch With Multi-Fuel Option Using Krill Herd Algorithm - et. al., Dr.S.Vijayaraj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents the application of the Krill Herd Algorithm to solve the Multi-Area Economic Load Dispatch Problem (MAED) by considering tie line constraint, valve point loading effect, and Multi-fuel option. The algorithm effectiveness is tested on a two-area system with six generating units. It is compared with Particle Swarm Optimization (PSO) algorithm and Genetic Algorithm (GA).